STUDI PENGUKURAN KECEPATAN ALIRAN PADA SUNGAI PASANG SURUT - Indra Setya Putra (Universitas Lambung Mangkurat, 2015)
Tidal river is one of the water resources which require proper management to be used as human needs such as irrigation and raw water. It required data such as discharge or velocity and water level. Until this period standard for measuring the velocity is just arranged in non-tidal rivers with SNI 03-2414-1991. This research aims to examine ways to measure water velocity in tidal rivers and provide recommendations for the design of new SNI for measuring the velocity of the tidal rivers.Methods used is by conducting velocity measurements performed in two rivers namely the Kapuas and Katingan by dividing the cross section into 3 sections and the time interval is 1 hour. Measurements were made using a 5 point in depth (d), are 20 cm, 0,2d, 0,4d, 0,6d, 0,8d which further results are elaborated and analyzed. It also carried out measurements of water level for 15 days with intervals of 1 hour.The results of this study are 8 requirements for the selection of the measurement location, 2 requirements for a long time and period measurement, 4 hydraulic conditions that must be considered at the time of measurement and 3 recommendations.Keywords : rivers, tidal, velocity measurement.